2021
DOI: 10.1111/nin.12402
|View full text |Cite
|
Sign up to set email alerts
|

Nurse navigators and person‐centred care; delivered but not valued?

Abstract: Positioning the individual at the centre of care (person‐centred care [PCC]) is essential to improving outcomes for people living with multiple chronic conditions. However, research also suggests that this is structurally challenging because health systems continue to adopt long‐standing, episodic care encounters. One strategy to provide a more cohesive, individualised approach to care is the implementation of the nurse navigator role. Current research shows that although PCC is a focus of navigation, such car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…The effectiveness of Nurse navigation is evident, as are the benefits of adequate training, shared decision-making and a structured, clear and well-understood referral process supported by the use of electronic system-incorporated prompts. However, despite the documented benefits of nurse navigation, implementation remains a challenge since patient-centred care is frequently impeded by the rigid, siloed structure of the health services, and this is an ongoing hurdle to overcome (Byrne et al , 2021). Notwithstanding this, the importance of careful patient navigation and oversight in achieving patient outcomes needs to be considered and emphasised in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of Nurse navigation is evident, as are the benefits of adequate training, shared decision-making and a structured, clear and well-understood referral process supported by the use of electronic system-incorporated prompts. However, despite the documented benefits of nurse navigation, implementation remains a challenge since patient-centred care is frequently impeded by the rigid, siloed structure of the health services, and this is an ongoing hurdle to overcome (Byrne et al , 2021). Notwithstanding this, the importance of careful patient navigation and oversight in achieving patient outcomes needs to be considered and emphasised in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are efforts to codesign care in ways that encompass the individuality of the person and are inclusive of their family. This orientation endeavours to disrupt episodic, siloed biomedical care (Angel, 2022; Byrne et al, 2021; White et al, 2021). Care partnerships between professionals and families have a significantly positive impact on families' perceptions of good care when family members' expertise about their loved one is recognised (Andersen et al, 2020; Quinney et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While this is a commendable notion, the operationalisation of PCC is often positioned with nurses, who have little authority to action the system‐wide changes needed to practice PCC. Indeed, recent research has suggested that PCC is more about maintaining the current, medically led system and changing the patient, more than it is about changing the system to meet the needs of individuals (Byrne, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in this area explored the existing tension between nurses' ability to deliver PCC in a system designed to maintain NPM efficiency, productivity and efficacy, and positioned PCC as a technology of compliance (Byrne, 2022), where individuals with chronic conditions are taught to care for themselves, omitting any genuine attempt to change system structures and models to meet their needs. The outcome of this previous research was a finding that PCC is often used as a way to ensure that people with chronic disease comply with societal norms, build self‐care skills and avoid ‘over’ using the hospital system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation